Da'wah Strategy of the Sunda Kelapa Taklim Council as a Non-State Actor in the Socialization of Islamic Family Law in Jakarta - Nupzahtusaniya Nupzahtusaniya; Andi Faisal Bakti; Yerik Tungatarov; Nurrohim Nurrohim (Universitas Muhammadiyah Bandung, 2026)
This study aims to analyze the role of the Sunda Kelapa Taklim Council as a non-state actor in the socialization of Islamic family law in Jakarta. Based on a qualitative descriptive approach with a case study design, this study examines how da'wah strategies are designed and implemented to transform family fiqh norms into the religious consciousness of urban communities. The focus of the research includes the material presented, delivery methods, communicative approaches, and the use of media in da'wah activities related to marriage issues, marital relations, divorce, and child care. Data was obtained through interviews, participatory observations, and documentation of the administrators, ustadz, and worshippers of the Sunda Kelapa Taklim Council centered at the Sunda Kelapa Grand Mosque. The results of the study show that the da'wah strategy functions as an effective instrument for socializing Islamic family law in shaping the normative awareness of the congregation. The substance of family law is conveyed in a normative-theological, ethical-social, and practical framework, so that it is not only understood as a formal rule, but as a spiritual mandate and moral guideline in domestic life. As a non-state actor, the taklim assembly does not have formal juridical authority like state institutions, but it plays a significant role in building moral legitimacy, providing a space for non-formal consultation before the litigation process, and bridging fiqh norms with national regulations and the realities of urban life. These findings confirm that the development of Islamic family law in Indonesia takes place through the interaction between the formal structure of the state and the dynamics of religious civil society that shape the understanding and practice of law at the social level.